Diffusion-Weighted Imaging in the Setting of Diffuse Cortical Laminar Necrosis and Hypoxic-Ischemic Encephalopathy - McKinney, Alexander M.; Teksam, Mehmet; Felice, Ross; Casey, Sean O.; Cranford, Ronald; Truwit, Charles L.; Kieffer, Stephen (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: As is the case for CT scans, MR images may occasionally appear deceptively normal unless proper windowing is used. We sought to illustrate the necessity for proper windowing and for assessing the gray–white matter differentiation on diffusion-weighted (DW) images in the setting of hypoxic-ischemic encephalopathy.METHODS: Six comatose patients (age range, 34–56 years) underwent MR imaging in the early phase (range, 1–5 days) after severe anoxic insult. T2-weighted, turbo fluid-attenuated inversion-recovery, and DW images were obtained in all six patients, with contrast-enhanced T1-weighted images obtained in four and apparent diffusion coefficient (ADC) maps in five of the six patients.RESULTS: At presentation, each of the six patients had symmetric, uniform hyperintensity in the cortex (mean ADC, 0.35 exttimes 10-3 mm2/s) relative to the white matter (mean ADC, 0.91 exttimes 10-3 mm2/s) on DW images. Each also had a poor outcome: brain death in four patients and a permanent vegetative state in two patients.CONCLUSION: The appearance of the MR images in the setting of diffuse cortical laminar necrosis can be deceptive to the unwary radiologist. The key to correct interpretation is proper windowing and the marked gray–white matter differentiation on spin-echo images but best seen on properly windowed DW images in the early subacute phase. This appearance also implies an extremely poor outcome, either a permanent vegetative state or brain death.